Spiritual Needs of Couples Facing Pregnancy Termination Because of Fetal Anomalies - Cowchock, F. Susan (Journal of pastoral care & counseling, 2011)
The spiritual needs of couples (9 mothers and 5 fathers) who were planning to terminate wanted second trimester pregnancies because of serious fetal anomalies were surveyed. Their greatest needs were for a “guidance from a higher power” and for “someone to pray for them.” Unlike other reported groups of patients, they did not want or expect their healthcare team to discuss their faith, or to pray with them. Most would prefer support from their own pastors, but their religious community was involved to only a small extent. They would welcome support from hospital chaplains, who could play a substantive and unique pastoral role in this clinical context.